Portable ground terminal for LEO satellite communication - Law, Choi Look (2008)
An introduction to the background approach taken in the project and achievements of the project is given in chapter 1. This is followed by a detail description of the portable ground terminal architecture in chapter 2. A brief introduction of the UOSAT-12 Merlion payload: satellite segment is made.